2015
DOI: 10.18544/pedm-21.02.0026
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for the discontinuation of therapy of personal insulin pump in children with type 1 diabetes

Abstract: The individual psycho-emotional state of the child and appropriate education are important at the start and continuation of CSII.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
(12 reference statements)
3
14
0
Order By: Relevance
“…CSII offers better flexibility in basal insulin adjustments and the management of exercise-associated hyperglycaemia (100). CSII is associated with reduced post-exercise hyperglycaemia compared to MDI (94), but can create frustrating challenges for sports requiring pump disconnection (101). CSII can also contribute to a greater sense of being "diseased" for some individuals and may promote stigma (101).…”
Section: Glucose Monitoring Cgm and Other Emerging Tools For Exercismentioning
confidence: 99%
See 1 more Smart Citation
“…CSII offers better flexibility in basal insulin adjustments and the management of exercise-associated hyperglycaemia (100). CSII is associated with reduced post-exercise hyperglycaemia compared to MDI (94), but can create frustrating challenges for sports requiring pump disconnection (101). CSII can also contribute to a greater sense of being "diseased" for some individuals and may promote stigma (101).…”
Section: Glucose Monitoring Cgm and Other Emerging Tools For Exercismentioning
confidence: 99%
“…CSII is associated with reduced post-exercise hyperglycaemia compared to MDI (94), but can create frustrating challenges for sports requiring pump disconnection (101). CSII can also contribute to a greater sense of being "diseased" for some individuals and may promote stigma (101). Prolonged pump disconnect (> 60 minutes) should be managed with reconnecting, testing and re-infusion if necessary, or a change to basal insulin provision by needle.…”
Section: Glucose Monitoring Cgm and Other Emerging Tools For Exercismentioning
confidence: 99%
“…For example, aerobic exercise may accelerate basal insulin absorption from the subcutaneous depot (74), whereas basal insulin glargine absorption is largely unaffected (99). Skin irritation, pump tubing, and wearing a pump that is visible to others can be concerns (100). In certain sports, such as basketball or contact sports, wearing pumps and other devices may be prohibited during competition.…”
Section: Use Of Csii and MDI For Activitymentioning
confidence: 99%
“…Reasons for discontinuing CSII therapy include greater sense of disease, difficulties in doing sports, poorer sense of well-being during CSII therapy, wearing an insulin pump, embarrassment, pain at the site of needle insertion, poor glycaemic control, fear and dislike of frequent blood glucose monitoring. [53][54][55] Qualitative work undertaken in a study of 19 parents with children aged < 12 years who had changed from MDI to CSII reported the benefits of CSII therapy to include no longer having to administer painful injections, fewer dietary restrictions, improved quality of family life and improved glycaemic control. 56 When patients and parents were interviewed in another study, they also reported improved glycaemic control, in addition to increased lifestyle flexibility and participation in social activities, during CSII therapy.…”
Section: Acceptability Of Continuous Subcutaneous Insulin Infusion Anmentioning
confidence: 99%